2011
DOI: 10.1016/j.neuroscience.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent alcohol exposure alters the central brain circuits known to regulate the stress response

Abstract: Adolescent alcohol exposure (AAE) may exert long-term effects on the adult brain. Here, we tested the hypothesis that the brain regions affected include the rat hypothalamic-pituitary-adrenal (HPA) axis. Specifically, we examined the consequences of AAE [postnatal days (PND) 28–42] on the HPA axis-related brain circuitry of male rats challenged with an intragastric (ig) administration of alcohol in young adulthood (PND 61–62). Adolescent rats were exposed to alcohol vapors, while controls did not receive the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 58 publications
3
42
1
Order By: Relevance
“…Specifically, CRF administration induces ICSS threshold elevations (Macey et al, 2000) and threshold elevations during ethanol withdrawal are reduced by a CRF antagonist (Bruijnzeel et al, 2010). Notably, adolescent ethanol exposure attenuates the adult CRF response to ethanol (Allen et al, 2011). A blunted CRF ethanol response may partly explain the diminished threshold elevations in response to acute ethanol and ethanol withdrawal (“hangover”) in AIE-exposed rats in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, CRF administration induces ICSS threshold elevations (Macey et al, 2000) and threshold elevations during ethanol withdrawal are reduced by a CRF antagonist (Bruijnzeel et al, 2010). Notably, adolescent ethanol exposure attenuates the adult CRF response to ethanol (Allen et al, 2011). A blunted CRF ethanol response may partly explain the diminished threshold elevations in response to acute ethanol and ethanol withdrawal (“hangover”) in AIE-exposed rats in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol exposure is known to attenuate the HPA response to stress [51]. Furthermore, blunted HPA axis responses to stress have been reported after adolescent ethanol exposure [31,32]. In the present studies, AIE exposure increased CRF mRNA levels in the CeA regardless of stress exposure, although the effect appeared to be more pronounced in non-stressed AIE-exposed rats (post hoc comparisons were not performed because there was no significant AIE × Stress interaction effect in the ANOVA).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the use of vapor exposure limits the potentially confounding effects of stress experienced during AIE exposure on risky choice under baseline conditions and in response to stress during adulthood. We showed previously that the AIE vapor exposure used in the present studies altered the adult CRF system in the hypothalamic-pituitary-adrenal axis that regulates the stress response [31,32]. Therefore, we also investigated the effects of acute and chronic social defeat stress in AIE vapor- and air-exposed rats.…”
Section: Introductionmentioning
confidence: 88%
“…All sections were maintained in an antifreeze solution (50% 0.1 M phosphate buffered saline, 20% glycerol, 30% ethylene glycol) at −20°C until analysis. Briefly, double DAB immunohistochemistry (IHC) staining was performed on free-floating sections as described previously (Choi et al, 2008, Allen et al, 2011b) with a rabbit anti-c-fos antibody (1:10,000, Calbiochem, San Diego, CA, USA) stained black and a sheep anti-PNMT antibody (1:7500, Chemicon/Millipore, Billerica, MA, USA) stained brown. Sections were mounted on gelatin-coated sub slides, dehydrated, and coverslipped using DPX mounting medium (Electron Microscopy Sciences, Hatfield, PA).…”
Section: Methodsmentioning
confidence: 99%
“…In adolescent self-administering binge-drinking animals, we found a decrease in the number of Crf cells in the young adult amygdala (Allen et al, 2011a), a brain region that is important in conveying the emotional component of the stress response (Pich et al, 1995). Additionally, we have shown that AIE exerts long-term effects on the ability of the PVN to respond to an alcohol challenge in young adulthood, possibly mediated by catecholaminergic input from the brain stem to the PVN as seen by changes in activation (measured via c-fos immunoreactivity) of phenylethanolamine N-methyltransferase (PNMT) neurons (Allen et al, 2011b, Logrip et al, 2013). These results prompted us to investigate whether AIE exposure similarly or differentially affects the response to a distinct acute stressor, an alcohol challenge in young adult and adult male rats.…”
Section: Introductionmentioning
confidence: 99%